Four Laws of Software. (Communications of the ACM, 2009)
The article presents the four laws of computer software, as defined by Nathan Myhrvold, former astrophysicist and chief technology officer (CTO) for Microsoft Inc. The laws explain the relationship between computer software code and the computer. A comparison of software and computers to gas which expands to fill a container is given.